1992
DOI: 10.1111/j.1752-1688.1992.tb03991.x
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL IMPACTS AND SOURCES OF SUSPENDED SOLIDS IN ONONDAGA CREEK, U.S.A.1

Abstract: The degradation of the optical aesthetics in the mouth of Onondaga Creek, New York, that occurs during high flow periods as a result of the influx of large quantities of suspended solids, is documented. Features of the degradation include very low clarity (Secchi disc minimum of approximately 0.1 m) and a brown ‘muddy’ appearance. The reduced clarity is mostly a result of increased light scattering. Loading and concentration profiles obtained for an approximately 35 km interval above the creek mouth over a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This type of association was observed infrequently in this study through visual microscopic observations. Johnson et al (1991) reported that increased inputs of watershed particles (particularly clay minerals; Effler et al, 1992) to oversaturated Onondaga Lake during high runoff intervals triggered increased CaCO 3 precipitation. Stumm & Morgan (1996) also noted that clay minerals can serve as heteronuclei for CaCO 3 precipitation.…”
Section: Origins Of Inorganic Tripton Interactions and Interannual mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of association was observed infrequently in this study through visual microscopic observations. Johnson et al (1991) reported that increased inputs of watershed particles (particularly clay minerals; Effler et al, 1992) to oversaturated Onondaga Lake during high runoff intervals triggered increased CaCO 3 precipitation. Stumm & Morgan (1996) also noted that clay minerals can serve as heteronuclei for CaCO 3 precipitation.…”
Section: Origins Of Inorganic Tripton Interactions and Interannual mentioning
confidence: 99%
“…The data array generated from IPA/ SAX provides flexibility in defining specific particle classes to account for statistically significant clusters of observations (e.g., calcite in hard water systems). The classification schemes for previous applications of IPA/SAX have ranged from rather detailed (15-20 explicit classes; Yin & Johnson, 1984;Effler et al, 1992) to more generalized approaches with fewer particle classes (three or four classes; Effler et al, 2002a).…”
Section: Ipa/sax Protocolmentioning
confidence: 99%
“…Measurements of particle projected area per unit volume (PAV in cm 2 /L) with IPA have been used to evaluate the optical impacts of inorganic tripton on light scattering and attenuation (Effler et al, 2000(Effler et al, , 2002a. Chemical characterization of particle populations by IPA has lead to resolution of the origins of inorganic tripton (Yin and Johnson, 1984;Effler et al, 1992Effler et al, , 2000Effler et al, , 2002a. Such information may be critical to managers to guide programs aimed at reducing related impacts on clarity, deposition, or material cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Pflüger et al (2010) demonstrated that the public had the lowest preference for rivers where turbidity and SSC are high. Similarly, the relationship between degraded aesthetic quality of surface waters and suspended sediment or turbidity has been reported in the literature (Effler et al 1992;Smith et al 1995;Bernal et al 1999;Bilotta and Brazier 2008).…”
Section: Introductionmentioning
confidence: 99%